2023
DOI: 10.3390/ijms242417192
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Lipid and Carotenoid Production via Rhodotorula paludigena CM33 Using Crude Glycerol as the Main Substrate: Pilot-Scale Experiments

Cheeranan Sriphuttha,
Pailin Boontawan,
Pasama Boonyanan
et al.

Abstract: Rhodotorula paludigena CM33 is an oleaginous yeast that has been demonstrated to accumulate substantial quantities of intracellular lipids and carotenoids. In this study, crude glycerol, a by-product of biodiesel production, was used as a carbon source to enhance the accumulation of lipids and carotenoids in the cells. The culture conditions were first optimized using response surface methodology, which revealed that the carotenoid concentration and lipid content improved when the concentration of crude glycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The authors reported an increase in carotenoid production of 42% in fed-batch culture. Sriphuttha et al [88] demonstrated a 12-fold increase in carotene production with the fed-batch strategy compared to batch.…”
Section: Submerged Fermentation Strategiesmentioning
confidence: 99%
“…The authors reported an increase in carotenoid production of 42% in fed-batch culture. Sriphuttha et al [88] demonstrated a 12-fold increase in carotene production with the fed-batch strategy compared to batch.…”
Section: Submerged Fermentation Strategiesmentioning
confidence: 99%
“…The strain Rhodotorula paludigena CM33, first isolated from castor seeds ( Ricinus communis ) 8 , has been identified for its significant lipid synthesis and carotenoid production capabilities 14 . Prior research by Sriphuttha et al 5 has extensively studied its effects on the growth, gene expression, intestinal microbial composition, disease resistance, and meat quality of whiteleg shrimp ( Litopenaeus vannamei ), demonstrating its potential as a probiotic supplement in shrimp feed.…”
Section: Introductionmentioning
confidence: 99%